2018
DOI: 10.1016/j.eclinm.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Carriage of NDM-5 and MCR-1 in Escherichia coli From Healthy People in Multiple Regions in China: A Cross Sectional Observational Study

Abstract: Background Carriage of carbapenem-resistant Enterobacteriaceae (CRE) in humans may contribute to the dissemination of CRE and impact on communities and healthcare facilities. Carbapenem-resistant Escherichia coli (CREC) is one of the major type of CRE in the human gut. Here, we describe a cross-sectional study to investigate the prevalence of CREC, and in particular the mcr-1 carrying CREC, in health volunteers in China. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 30 publications
1
60
0
1
Order By: Relevance
“…The ϳ50-kb plasmids carrying bla NDM were confirmed to be IncX3 type by using primers covering both the backbone of IncX3 plasmid and bla NDM genes. Totally, among the 110 NDM producers, 87 (79.1%) bla NDM genes were carried by IncX3 plasmids (Table S2), which was consistent with previous reports that the IncX3 plasmid was a major vector driving the transmission of bla NDM (7,12,13,18). IncX3 plasmid was first associated with the dissemination of bla NDM-1 among clinical CRE strains (19).…”
supporting
confidence: 88%
“…The ϳ50-kb plasmids carrying bla NDM were confirmed to be IncX3 type by using primers covering both the backbone of IncX3 plasmid and bla NDM genes. Totally, among the 110 NDM producers, 87 (79.1%) bla NDM genes were carried by IncX3 plasmids (Table S2), which was consistent with previous reports that the IncX3 plasmid was a major vector driving the transmission of bla NDM (7,12,13,18). IncX3 plasmid was first associated with the dissemination of bla NDM-1 among clinical CRE strains (19).…”
supporting
confidence: 88%
“…Carbapenem-resistant Enterobacteriaceae is mediated largely by the production of carbapenemase especially for NDM isolates. NDM-5, an NDM-1 variant, exhibited increased enzyme activity to carbapenems (Rogers et al, 2013) and its gene bla NDM-5 has been reported worldwide (Khan et al, 2017) and is the most prevalent variant in China (Shen et al, 2018). In support of this, 84 (52%) NDM-5-producing E. coli were collected from 161 bla NDM carrying CRE in chickens (Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 81%
“…In this study, mcr-1 and bla NDM-5 are the most dominant (78.6%, 11/14) combination among MCR-CREC strains. Escherichia coli isolates carrying both mcr-1 and bla NDM-5 also have disseminated among healthy people in various regions of China [48]. The pattern of transmission of resistance genes between patients and healthy individuals should also be carefully monitored.…”
Section: Discussionmentioning
confidence: 99%